1995
DOI: 10.3109/09513599509160450
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged treatment of hirsutism with flutamide alone in patients affected by polycystic ovary syndrome

Abstract: Hirsutism is a common symptom of women affected by polycystic ovary syndrome (PCOS). The effectiveness of the antiandrogen flutamide alone was studied in 25 patients affected by PCOS with severe hirsutism for a period of 24 months. Seventeen of these patients had not been treated before and eight had had previous but unsatisfactory therapy. Nineteen patients showed a normal body weight (BMI < 25 kg/m2) whereas six were obese (BMI > 35 kg/m2). A chemical and endocrinological evaluation and an assessment of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…In agreement with our findings, many authors report that flutamide does not significantly modify hormone parameters (29,32), while other studies show a significant decrease in T and DHEAS, favoring the hypothesis that flutamide may reduce androgen synthesis (inhibiting the 17,20 desmolase adrenal activity) or increase androgen catabolism (24,33,34).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In agreement with our findings, many authors report that flutamide does not significantly modify hormone parameters (29,32), while other studies show a significant decrease in T and DHEAS, favoring the hypothesis that flutamide may reduce androgen synthesis (inhibiting the 17,20 desmolase adrenal activity) or increase androgen catabolism (24,33,34).…”
Section: Discussionsupporting
confidence: 81%
“…Investigators who used both drugs with the same dosage as ourselves for 6-12 months report that finasteride decreases the Ferriman-Gallwey score from 11% (25) to 63.8% (26) in PCOS and from 10.6% (27) to 63% (28) in idiopathic hirsutism. Findings with flutamide range from 36.4% (29) to 53% (30) in PCOS and from 30.1% (31) to 70.9% (24) in idiopathic hirsutism.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have suggested that flutamide reduces both adrenal and ovarian androgen synthesis [55][56][57] , restores ovulation and ameliorates the metabolic profile of hyperandrogenic women 30,31 , whereas other reports have suggested no substantial effects on circulating androgens, lipids, or insulin sensitivity 32-37 . In our study, flutamide decreased androgen levels, but failed to improve insulin sensitivity in non-obese PCOS women after a short therapy period.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to our study, some reports suggest that flutamide works by reducing both adrenal and ovarian androgen synthesis, 5-7 whereas others have documented that flutamide has no substantial effect on circulating androgens, lipids or insulin sensitivity. [8][9][10][11] It is known that combined OCs can reduce circulating androgen levels through the suppression of circulating LH and the stimulation of sex hormonebinding globulin (SHBG) levels. 3 CPA/EE has previously been reported to significantly decrease total and free testosterone, androstenedione, DHEAS, and DHT levels and increase SHBG levels in hyperandrogenic hirsute women.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Some reports suggest that flutamide achieves this via a reduction in both adrenal and ovarian androgen synthesis; 5-7 however, others document no substantial effects on circulating androgens, lipids or insulin sensitivity following treatment with flutamide. [8][9][10][11] In terms of dosage the efficacy of low-dose flutamide therapy on hirsutism has been observed to be similar to that of higher daily doses (500-750 mg) used either alone or in combination with an OC. [5][6][7][8] When long-term treatment is anticipated, the use of a low dose reduces both the cost of therapy and the likelihood of side effects.…”
Section: Introductionmentioning
confidence: 91%